2022
DOI: 10.3390/ijerph19052756
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Job Loss during the COVID-19 Pandemic: Mediation by Hopelessness and Moderation by Trait Emotional Intelligence

Abstract: This study contributes to the knowledge on the effects of the COVID-19 pandemic by examining a moderated mediation model in which the impact of job loss over quality of life (QoL) is mediated by hopelessness and moderated by trait emotional intelligence (trait EI). Data were collected from a large nationally representative Italian sample of adult workers (N = 1610), who completed a series of anonymous online questionnaires. Total, direct and indirect effects were estimated through bootstrapped mediated moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In a meta-analysis, Miao et al (2016) concluded that leaders' emotional intelligence strongly predicted followers' job satisfaction, and followers' emotional intelligence played a significant mediating role in this link. Andrei et al (2022) similarly revealed that trait emotional intelligence moderated the direct predictive effects of unemployment on the quality of life during the pandemic.…”
Section: Introductionmentioning
confidence: 87%
“…In a meta-analysis, Miao et al (2016) concluded that leaders' emotional intelligence strongly predicted followers' job satisfaction, and followers' emotional intelligence played a significant mediating role in this link. Andrei et al (2022) similarly revealed that trait emotional intelligence moderated the direct predictive effects of unemployment on the quality of life during the pandemic.…”
Section: Introductionmentioning
confidence: 87%
“…The pandemic-induced economic downturn has resulted in widespread job losses and reduced employment opportunities (Andrei et al, 2022). NEETs, who were already struggling to find employment before the economic crisis (Sergi et al, 2018), now face even greater difficulties (Aina et al, 2021;Cefalo & Scandurra, 2021;Siza, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is closely related to an individual's ability to socialize, make decisions, and cope with stress. Mental health, on the other hand, encompasses emotional, cognitive, and behavioral well-being, and it has a significant impact on an individual's quality of life and academic performance (Andrei et al, 2022). However, although emotional intelligence and mental health play a key role in the overall growth of individuals, there are still many unanswered questions about their relationship with academic performance (Chu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%